Identification of financial strategy in small & medium-sized entrepreneurship - Svatošová, Veronika (Mendelova univerzita v Brně, 2017)
This paper deals with the importance of financial strategy development of small and medium-sized enterprises (SMEs) in the winery industry. The main objective of the paper is to identify the current financial strategy of small and medium-sized enterprises and afterwards to propose changes that lead to new financial strategy. The research methods are the selected methods of financial analysis, collecting data about the research sample of SMEs, modelling the financial strategy with the help of Vensim program and further simulation of this model in business practice. The model derives from the previous research activities. The purpose of this paper is also to verify the usage of theoretically created model in small and medium-sized entrepreneurship and find the optimal financial strategy in the area examined. The results of this paper show the selected area of small and medium-sized entrepreneurship uses mainly the financial strategy of maximum liquidity (conservative strategy) in all observed years (2010-2014). This means the selected research sample of SMEs do not use progressive investment strategy with a further development. This result could highlight that SMEs in agricultural sector do not meet the financial strategy with corporate strategy focused on other business development. It is recommended to change this strategy into balancedfinancial strategy focused on higher profitability that could be used for the other expansion and development of the company.
Keywords: Agricultural enterprises; Financial analysis; Financial strategy; Financial strategy model; Modelling; Simulation; Small & medium-sized enterprises; Vensim program